Probiotics for Clostridium difficile infection in adults (PICO): Study protocol for a double-blind, randomized controlled trial - Barker, Anna (Contemp Clin Trials, 2015)
BACKGROUND: Clostridium difficile is a pathogen of rapidly increasing public health importance. An estimated quarter of a million Clostridium difficile infections (CDI) occur in the United States annually, at a resultant cost of 14,000 deaths and 1 billion dollars. Clostridium difficile related deaths have risen 400% over the last decade, and current standard antibiotic treatments are only 75 to 85% successful. Besides increasing the risk of antibiotic resistance and side effects, these treatments are very expensive. The most vulnerable population for Clostridium difficile is older adults, who make up approximately half of the cases, but account for 90% of the related deaths. Probiotics may have potential as adjunctive therapeutic agents for CDIs, however, current data is limited. METHODS: This pilot study is a single-site, randomized, placebo-controlled, double-blind, phase two clinical trial. The trial primarily evaluates the effect of four weeks of probiotic therapy in addition to standard of care on Clostridium difficile diarrhea duration and recurrence. Secondary outcomes include effect on fecal cytokines, fecal lactoferrin, and Clostridium difficile toxin density in stool, as well as patient functional status. DISCUSSION: This pilot study will determine the feasibility and effect size to conduct larger randomized controlled trials of probiotic interventions in patients with CDI, to determine the impact of probiotics on the symptoms of CDI.